THE MODERATING ROLE OF PROFITABILITY IN THE FIELD OF ANALYZING THE EFFECT OF EXCHANGE RATES, TAX PLANNING AND AGENCY COSTS ON TRANSFER PRICING - Fitriani, Azizah; Anam, Saiful; Wardhana, Rony (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to determine the causal relationship between exchange rate, tax planning, and agency costs on transfer pricing, and to examine the moderating role of profitability within transportation and logistics companies in Indonesia. Design/Methodology/Approach: The study employs a causal-associative approach using secondary data from financial statements of transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. A purposive sampling method was used to select 14 companies from a population of 27 firms. Data analysis was performed using Partial Least Squares (PLS) with SmartPLS software. Findings: The results indicate that agency cost and tax planning have a positive and significant effect on transfer pricing, while the exchange rate shows no significant effect. Profitability significantly moderates the relationship between exchange rate and tax planning on transfer pricing in a negative direction, but does not moderate the effect of agency costs on transfer pricing. Research limitations/implications: This study is limited to transportation and logistics companies listed on the IDX and uses secondary data, which may limit the generalizability of findings. Future researchers are encouraged to expand the scope across sectors or incorporate additional moderating variables. Practical implications: The findings suggest that regulators need to strengthen oversight of transfer pricing practices, particularly among firms with high leverage. Companies are encouraged to comply with the arm's length principle to maintain financial credibility and minimize tax-related risks. Originality/value: This study offers novelty by integrating profitability as a moderating variable in examining the relationship between agency costs, exchange rates, tax planning, and transfer pricing—an area that remains underexplored within Indonesia's transportation and logistics industry.